Distribution, diastereomer-specific accumulation and associated health risks of hexabromocyclododecanes (HBCDs) in soil-vegetable system of the Pearl River Delta region, South China. (15th October 2019) - Lü, Huixiong; Ma, Xiao-Jing; Huang, Xue-Jing; Lu, Shaoyou; Huang, Yu-Hong; Mo, Ce-Hui; Cai, Quan-Ying; Wong, Ming-Hung
Abstract: The distribution and diastereomeric profiles of hexabromocyclododecanes (HBCDs, identified as persistent organic pollutants) in soil-vegetable system of open fields remain unknown. In this study, three main HBCD diastereoisomers (α-, β-, and γ-HBCDs) were analyzed in paired soil and vegetable samples from vegetable farms in four cities (Guangzhou, Jiangmen, Huizhou, Foshan) of the Pearl River Delta region, Southern China. The sum concentrations of the three diastereoisomers (∑HBCDs) in soils varied from 0.99 to 18.4 ng/g (dry weight) with a mean of 5.77 ng/g, decreasing in the order of Jiangmen > Guangzhou > Huizhou > Foshan. The distributions of HBCDs in both soil and vegetable were diastereomer-specific, with γ-HBCD being predominant. The ∑HBCDs in vegetables ranged from 0.87 to 32.7 ng/g (dry weight) with a mean of 16.6 ng/g, generally higher than those of the corresponding soils. Thus bioconcentration factors (BCFs, the ratio of contaminant concentration in vegetable to that in soil) of HBCDs were generally greater than 1.0, implying higher accumulation in vegetable. The estimated daily intake (EDI) of ΣHBCDs via consumption of vegetables varied from 0.26 to 9.35 ng/kg bw/day with a mean of 3.60 ng/kg bw/day for adults and from 0.32 to 11.5 ng/kg bw/day with a mean of 4.41 ng/kg bw/day for Children, far lower than the oral reference dose (RfD, 2 × 10 5  ng/kg bw/day) proposed by US National Research Council. These results suggest that HBCD in the vegetables posed low health risk for the local population. These data are the first report on HBCD occurrence and health risk in soil-vegetable system of open fields. Graphical abstract: Image 1 Highlights: Occurrence of HBCD in soil-vegetable system of open field was firstly reported. HBCD distributions in both soil and vegetable were diastereomer-specific. HBCDs in vegetables presented high accumulation, but posed low health risk.